The 6-GHz methanol multibeam maser catalogue – I. Galactic Centre region, longitudes 345° to 6° - Caswell, J.; Fuller, G.; Green, A.; Avison, A.; Breen, S.; Brooks, K.; Burton, M.; Chrysostomou, A.; Cox, J.; Diamond, P.; Ellingsen, S.; Gray, M.; et al. (Oxford University Press, 2010)
We have conducted a Galactic plane survey of methanol masers at 6668 MHz using a seven-beam receiver on the Parkes telescope. Here we present results from the first part, which provides sensitive unbiased coverage of a large region around the Galactic Centre. Details are given for 183 methanol maser sites in the longitude range 345° through the Galactic Centre to 6°. Within 6° of the Galactic Centre, we found 88 maser sites, of which more than half (48) are new discoveries. The masers are confined to a narrow Galactic latitude range, indicative of many sources at the Galactic Centre distance and beyond, and confined to a thin disc population; there is no high-latitude population thatmight be ascribed to the Galactic bulge. Within 2° of the Galactic Centre the maser velocities all lie between -60 and +77kms-1, a range much smaller than the 540kms-1 range observed in CO.Elsewhere, the maser with highest positive velocity (+107kms-1) occurs, surprisingly, near longitude 355° and is probably attributable to the Galactic bar. The maser with the most negative velocity (-127kms-1) is near longitude 346°, within the longitude-velocity locus of the near side of the `3-kpc arm'. It has the most extreme velocity of a clear population of masers associated with the near and far sides of the 3-kpc arm. Closer to the Galactic Centre the maser space density is generally low, except within 0.25 kpc of the Galactic Centre itself, the `Galactic Centre zone', where it is 50 times higher, which is hinted at by the longitude distribution, and confirmed by the unusual velocities.